Pembiasaan Perilaku Religius Pada Siswa Kelas IV Di Sekolah Dasar Islam Terpadu (SD IT) Cita Mulia Ajibarang - Asma Azzahra (Journal of Primary Education Studies, 2025)
This study aims to examine the habituation of religious behavior among fourth-grade students at SD IT Cita Mulia Ajibarang using a qualitative approach and field study. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results show that students regularly practice daily prayers, Dhuha prayer, Tahsin Wafa, Quran memorization, congregational prayers, Murajaah, as well as habits of cleanliness and healthy living. The success of this habituation is supported by the cooperation of the school and parents, while obstacles include diverse student backgrounds, lack of awareness, and limited school facilities. Efforts to overcome these challenges are carried out through weekly evaluations, personal approaches, and improvement of infrastructure and facilities.